Predictors and outcomes of angioplasty and stenting in acute intracranial atherosclerosis-related vertebrobasilar artery occlusion - Seol Bin Park; Byung Hyun Baek; Yun Young Lee; Seul Kee Kim; Chan Park; Byung Chan Lee; Hyoung Ook Kim; Woong Yoon (Frontiers in Neurology)
ObjectiveThis study aimed to investigate clinical outcomes and predictors of favorable functional outcomes after endovascular treatment, including emergent angioplasty and stenting, in patients with intracranial atherosclerotic stenosis (ICAS)-related occlusions in vertebrobasilar arteries.Materials and methodsThis retrospective case series included 46 patients with acute occlusions of vertebrobasilar arteries, due to underlying ICAS. All patients underwent a thrombectomy, followed by angioplasty and/or stenting. We performed logistic regression analyses to identify independent predictors of favorable outcomes. A favorable outcome was defined as a score of 0–3 on the 90-day modified Rankin Scale.ResultsOverall, successful reperfusion was achieved in 44/46 (95.7%) patients and 90-day favorable outcomes were achieved in 21/46 patients (45.7%). The 90-day mortality rate was 23.9% (11/46). In a multivariate binary logistic analysis, independent predictors of favorable outcome were hyperlipidemia (OR = 7.866, 95% CI: 1.093–56.590, p = 0.040), admission hyperglycemia (OR = 0.144, 95% CI: 0.023–0.914, p = 0.040), basilar artery occlusion (OR = 0.086, 95% CI: 0.008–0.907, p = 0.041), and treatment with angioplasty alone (OR = 9.779, 95% CI: 1.022–93.525, p = 0.048).ConclusionOur findings suggested that emergent angioplasty and/or stenting could yield high rates of successful reperfusion and favorable outcomes in patients with ICAS-related occlusions in vertebrobasilar arteries. Our study also demonstrated that hyperlipidemia and treatment with angioplasty alone were associated with favorable outcomes, in contrast, admission hyperglycemia and basilar artery occlusion were associated with unfavorable outcomes in these patients.